Engagement in Advance Care Planning and Surrogates' Knowledge of Patients' Treatment Goals. Issue 8 (20th March 2017) - Fried, Terri R.; Zenoni, Maria; Iannone, Lynne; O'Leary, John; Fenton, Brenda T.
Abstract : Objectives: A key objective of advance care planning (ACP) is improving surrogates' knowledge of patients' treatment goals. Little is known about whether ACP outside of a trial accomplishes this. The objective was to examine patient and surrogate reports of ACP engagement and associations with surrogate knowledge of goals. Design: Cohort study Setting: Primary care in a Veterans Affairs Medical Center. Participants: 350 community‐dwelling veterans age ≥55 years and the individual they would choose to make medical decisions on their behalf, interviewed separately. Measurements: Treatment goals were assessed by veterans' ratings of 3 health states: severe physical disability, cognitive disability, and pain, as an acceptable or unacceptable result of treatment for severe illness. Surrogates had knowledge if they correctly predicted all 3 responses. Veterans and surrogates were asked about living will and health care proxy completion and communication about life‐sustaining treatment and quality versus quantity of life (QOL). Results: Over 40% of dyads agreed that the veteran had not completed a living will or health care proxy and that there was no QOL communication. For each activity, sizeable proportions (18–34%) disagreed about participation. In dyads who agreed QOL communication had occurred, 30% of surrogates had knowledge, compared to 21% in dyads who agreed communication had not occurred and 15% in dyads who disagreed ( P = .01). This relationship persisted in multivariable analysis. Agreement about other ACP activities was not associated with knowledge. Conclusion: Disagreement about ACP participation was common. Agreement about communication regarding QOL was modestly associated with surrogate knowledge of treatment goals. Eliciting surrogates' perspectives is critical to ACP. Even dyads who agree about participation may need additional support for successful engagement.